Atomic Scale Simulation on the Fracture Mechanism of Black Phosphorus Monolayer under Indentation - Liu, Yang (Nanomaterials (Basel), 2018)
Molecular dynamics simulations on the indentation process of freestanding and Pt(111)-supported black phosphorus (BP) monolayer were conducted to study the fracture mechanism of the membrane. For the freestanding BP monolayer, crack grows firstly along armchair direction and then zigzag direction during the indentation process. Whereas, for the Pt(111)-supported BP monolayer, crack growth shows no obvious directionality, with irregular distribution of crack tips. Further study on stress distribution shows that maximum normal stress component at elastic stage is in zigzag direction for the freestanding BP monolayer, and in vertical direction for the Pt(111)-supported BP monolayer. As BP monolayer is remarkably anisotropic for in-plane mechanical properties and homogeneous for out-of-plane mechanical properties, the difference of stress state may be a key reason for the different fracture behavior in these two cases. These findings may help to understand the failure mechanism of BP, when applied in nano-devices.